Rethinking the question of identity for indigenous public administration within public administration - Mahlala Sandiso ,Basheka Benon and Rapanyane Makhura Benjamin (International journal of research in business and social science., 2024)
In African Public Administration, this article considers the subject of rethinking identity for indigenous public administration. It seeks to determine whether the lack of indigenous traditions as a foundation for current Public Administration will actually fulfil the essential knowledge demands of government by solving challenges that cannot be answered by public officials. This epistemic discrimination of indigenous public administration in Public Administration has been widely disseminated without taking into account the value systems of African societies that have established their own distinct administrative structures within their respective cultural settings. This has resulted in a plethora of misunderstandings and contradictions in contemporary public administration practices. This is due to P[p]ublic A[a]dministration modulating the influence of Africans, their processes and institutions in the development of the discipline. In light of this realization, this paper discusses how rethinking the issue of identity for indigenous public administration can and should serve as a foundational tool for promoting Africa's Public Administration. This paper employs Afrocentricity as an avant-garde to untangle this discourse based on the above-mentioned breakdown. The paper is conceptual in nature and is based on a review of literature from a variety of sources, including policies, popular media statements, and academic publications.